Lethrus (Lethrus) schneideri sp. n. (Coleoptera, Geotrupidae) from Greece - Král, David; Hillert, Oliver; Drožová, Dana; Sípek, Petr (ZooKeys, 2013)
Lethrus (Lethrus) schneideri Král & Hillert, sp. n. from Thrace, Greece, is described. The new species is morphologically most similar and probably closely related to Lethrus (Lethrus) apterus (Laxmann, 1770) and Lethrus (Lethrus) ares Král, Rejsek & Schneider, 2001. Diagnostic characters (shape of mandibles, ventral mandible processes, pronotum and parameres) are illustrated. Character matrix for separation of males of the Lethrus species closely related to Lethrus schneideri Král & Hillert, sp. n. and geographic ranges for all species studied are mapped.
Keywords: Lethrus; new species; Lethrinae; Palaearctic region; Mediterranean; Geotrupidae